Thermo-Mechanical And Adhesion Performance Of Silver-Filled Conductive Polymer Composite (SFCP) Using Thermoplastic Polyurethane (TPU) Substrate - Omar, Ghazali; A Hamid, Husna; Azli, Siti Ashikin; Jasmee, Solehah; Jalar, Azman; Tamaldin, Noreffendy; Che Ani, Fakhrozi (Universiti Malaysia Perlis, 2020)
Emerging of conductive metal filler in nanoscale like Silver-Filled Conductive Polymer Composite (SFCP) ink is one of the important technology for electronic interconnects future. Among the key challenges in the successful development of such materials are to offer high electrical conductivity and good adhesion in polymer-based substrates without compromising on the mechanical reliability of such devices. This paper discussed the characteristics of Thermoplastic Polyurethane (TPU) based-materials in terms of their sustainability, wettability and SFCP conductivity of thermal effect (room temperature –25°C), 40°C, 60°C and 80°C). The experimental work involved electrical conductivity measurement using a Four-Point Probe, contact angle measurement and surface roughness analysis. Surface morphology analysis was carried out by using Axioscope 2MAT Optical Microscope and Scanning Electron Microscopic (SEM). The results show that sheet resistance of SFCP increased with an increasing strain and decrease with the increasing of temperature. The above results were observed due to the crack formation against strain but the presents of temperature cause the silver (Ag) particle to expand, filled the gap and form network path for electrical conduction even at maximum temperature and strain (80°C at 80%). Moreover, the TPU shows low wettability that exhibits poor adhesion between SFCP and TPU substrate due to reducing in the contact area between adhesive and substrate that cause the surface has low surface energy when exposed to variation of temperature.